Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/aur.2358
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gut Microbiota of Children with Autism Spectrum Disorder

Abstract: Alterations in the gut microbiota may influence gastrointestinal (GI) dysbiosis frequently reported in individuals with autism spectrum disorder (ASD). In this study, we sequenced the bacterial 16S rRNA gene to evaluate changes in fecal microbiota between 48 children with ASD and 48 healthy children in China. At the phylum level, the number of Firmicutes, Proteobacteria, and Verrucomicrobia decreased in children with ASD, while the Bacteroidetes/Firmicutes was significantly higher in autistic children due to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(156 citation statements)
references
References 60 publications
7
110
1
Order By: Relevance
“…Autism spectrum disorder is associated with the dysregulation of glutamate, dopamine, and serotonin in the brains of patients [ 99 , 100 , 101 ]. Increases of Bacteroides , Prevotella , Lachnospiracea_incertae_sedis , and Megamonas as well as decreases of Clostridium XlVa , Eisenbergiella , Clostridium IV , Flavonifractor , Escherichia / Shigella , Haemophilus , Akkermansia , and Dialister have been detected in patients with autism [ 102 ]. Glutamate metabolism is associated with the alterations of gut microbiota composition in patients with autism [ 36 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…Autism spectrum disorder is associated with the dysregulation of glutamate, dopamine, and serotonin in the brains of patients [ 99 , 100 , 101 ]. Increases of Bacteroides , Prevotella , Lachnospiracea_incertae_sedis , and Megamonas as well as decreases of Clostridium XlVa , Eisenbergiella , Clostridium IV , Flavonifractor , Escherichia / Shigella , Haemophilus , Akkermansia , and Dialister have been detected in patients with autism [ 102 ]. Glutamate metabolism is associated with the alterations of gut microbiota composition in patients with autism [ 36 ].…”
Section: Influence Of Gut Microbe-regulated Neurotransmitter Synthesis On Cognitionmentioning
confidence: 99%
“…DNA extraction and PCR amplification were performed as described previously (Zou et al, 2020). Specially, the fecal DNA was extracted using the QIAamp DNA Stool Mini Kit (QIAGEN, Hilden, Germany).…”
Section: Genomic Dna Extraction Pcr Amplification and 16s Rrna Genementioning
confidence: 99%
“…Sequencing data was analyzed using Mothur (version 1.39.5) (Schloss, Gevers & Westcott, 2011) as previously described (Zou et al, 2020). In brief, the reads containing ambiguous bases, length shorter than 350 base pairs, with chimeric sequence or contaminant sequence were firstly removed.…”
Section: Bioinformatics and Statistical Analysismentioning
confidence: 99%
“…Lachnospiraceae belongs to Clostridium of the phylum Firmicutes, and it can ferment glucose to produce formic acid, lactic acid, acetic acid. At the genus level, Flavonifractor was higher in female adults, which also belongs to the phylum Firmicutes and can synthesize short-chain fatty acids from plant polysaccharides ( Zhang et al, 2020a ; Zhang et al, 2020b ; Zou et al, 2020 ; Mikami et al, 2020 ). The results of Bo et al (2019) showed that the most abundant bacteria in the cecum of captive Brandt’s voles are Firmicutes and Bacteroides, accounting for about 91%, while the content of Proteobacteria is low.…”
Section: Discussionmentioning
confidence: 99%